Patients' Expectations of osteotomies around the knee. Issue 6 (28th June 2019) - Grünwald, Leonard; Angele, Peter; Dickschas, Jörg; Schröter, Steffen; Saier, Tim
Aims and Objectives: This multicentre study was conducted to investigate patients' expectations on osteotomies around the knee in different health-related domains. It was hypothesized that these expectations are high, yet realistic. Materials and Methods: A total of 264 Patients (age 47y±11) were enrolled from March 2015 until May 2016 in seven specialised departments of orthopaedic surgery in Germany. Data was collected via a standardized questionnaire relating to the expected outcomes of osteotomies around the knee 24 h to 48 h prior to surgery. In addition, KOOS and selfefficacy were assessed. Results: According to the KOOS results all patients suffered from a burden due to their knee impairments; women suffered significantly more than men. All participants had high expectations in all domains concerning the surgical outcome. For patients who had a high work intensity the ability to keep stressful working postures was even more important than for the others (i.e. to kneel, to squat). Furthermore, a lower quality of life was associated with higher importance of improving the ability to walk, to achieve improvements in daily activities and social well-being. Conclusion: Patients' expectations of osteotomies around the knee are high, and mostly outperform the average results reported in the literature. Detailed patient information giving an overview of the realistic results of osteotomies around the knee seems to be mandatory to prevent patients' dissatisfaction.